Meniscus progenitor cells combined with joint lavage promote meniscus regeneration and cartilage protection in rat models - Guo, Shu-Yang; Zhu, Jia-Hao; Yan, Wan-Ting; Huang, Xiao-Jia; Xu, Wen-Nan; Wang, Jing-Song; Zhang, Zheng-Zheng (Frontiers in Bioengineering and Biotechnology, 2026)
The meniscus plays a crucial role in knee joint function, yet its limited intrinsic regenerative capacity, particularly within the avascular region, makes meniscal injuries a major therapeutic challenge. Meniscus progenitor cells (MPCs) have shown potential to promote meniscal regeneration, but their efficacy may be compromised in the inflammatory microenvironment. Joint lavage, a simple and clinically applied procedure that reduces intra-articular inflammation, may enhance the outcomes of cell-based therapies. Here, we investigated the therapeutic efficacy of combining joint lavage with MPC transplantation in rat partial meniscectomy models and further examined the effects of interleukin-1β (IL-1β), a key inflammatory mediator, on MPC function in vitro. Lavage significantly reduced intra-articular levels of multiple inflammatory cytokines, including IL-1β, which otherwise impaired MPC migration, proliferation, chondrogenic differentiation, and gene expression. In vivo, combined lavage and MPC therapy promoted more complete meniscal regeneration, enhanced type II collagen deposition, preserved cartilage integrity, and improved biomechanical properties compared with either treatment alone. These findings demonstrate that preconditioning the joint microenvironment through lavage markedly augments the regenerative potential of MPCs, providing a simple, low-cost, and clinically feasible strategy to improve meniscus and cartilage repair under inflammatory conditions.